Penerapan Metode Waterfall dalam Pengembangan Aplikasi Akuntansi untuk Kontraktor dengan Pemrograman PHP: Studi Kasus PT. Mayo Nuwantara - Yulianti, Dea; Marsyah, Aulia; Dwiputri, Suhadah; W, Okta; Fajriyah, Fajriyah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
PT Mayo Nuwantara is a company that focuses on development consulting services. Based on the analysis conducted, it was found that the financial reporting process still uses a recording method that copies records to the general ledger, which is then entered into MS Excel so that the resulting report arrives late and is inaccurate. Therefore, the author created a system by developing a web-based financial reporting application using the waterfall method which includes software needs analysis, design, coding, and testing. The data collection methods used include observation, interviews, and literature studies. The designed system provides features according to user levels, namely admin, chief financial officer, and director. Admin and chief financial officer have the ability to manage account groups, account group details, and cash receipts and disbursements data. In addition, they can also access the general journal, general ledger, income statement, and balance sheet report. On the other hand, the director has the authority to manage user data and can also access vital information such as the general journal, general ledger, income statement, and balance sheet report. Meanwhile, the director can manage user data, as well as access the general journal, general ledger, income statement, and balance sheet report. This system is expected to improve performance in processing financial reports at PT Mayo Nuwantara